Menthol-Induced Chirality in Semiconductor Nanostructures: Chiroptical Properties of Atomically Thin 2D CdSe Nanoplatelets Capped with Enantiomeric L-(−)/D-(+)-Menthyl Thioglycolates - Maria Yu. Skrypnik; Daria A. Kurtina; Sofia P. Karamysheva; Evgeniia A. Stepanidenko; Irina S. Vasil’eva; Shuai Chang; Alexander I. Lebedev; Roman B. Vasiliev (Nanomaterials)
Semiconductor colloidal nanostructures capped with chiral organic molecules are a research hotspot due to their wide range of important implications for photonic and spintronic applications. However, to date, the study of chiral ligands has been limited almost exclusively to naturally occurring chiral amino and hydroxy acids, which typically contain only one stereocenter. Here, we show the pronounced induction of chirality in atomically thin CdSe nanoplatelets (NPLs) by capping them with enantiopure menthol derivatives as multi-stereocenter molecules. L-(−)/D-(+)-menthyl thioglycolate, easily synthesized from L-(−)/D-(+)-menthol, is attached to Cd-rich (001) basal planes of 2- and 3-monolayer (ML) CdSe NPLs. We show the appearance of narrow sign-alternating bands in the circular dichroism (CD) spectra of 2 ML NPLs corresponding to heavy-hole (HH) and light-hole (LH) excitons with maximal dissymmetry g-factor up to 2.5 × 10−4. The most intense CD bands correspond to the lower-energy HH exciton, and in comparison with the N-acetyl-L-Cysteine ligand, the CD bands for L-(−)-menthyl thioglycolate have the opposite sign. The CD measurements are complemented with magnetic CD measurements and first-principles modeling. The obtained results may be of interest for designing new chiral semiconductor nanostructures and improving understanding of their chiroptical properties.